Functional evaluation of diabetic patients with foot ulcers - Fernando, Thiago Santos; Borges, Vinicius Quadros; Ferraz, Gabriel Ferreira; Stéfani, Kelly Cristina (Scientific Journal of the Foot & Ankle, 2018)
Objective: The objective of this study was to perform a functional evaluation of diabetic patients with plantar ulcers using the American Orthopaedic Foot and Ankle Society (AOFAS) score. Methods: In this prospective cohort study, 50 diabetic patients treated in an outpatient clinic under conservative management were consecutively evaluated for active ulcers on the foot. The ulcer mean progression time, size and classification and the AOFAS score were evaluated. Results: Among the sample, 38 (76%) were men, the mean age was 64 years, and the mean body mass index was 28.27 kg/m2. The mean ulcer progression time was 9 months, and 40 (80%) patients were classified as Wagner grade 1. There was a significant difference in AOFAS scores between ulcer grades. Conclusion: The AOFAS score can be used for functional evaluation in diabetic patients with ulcers. However, due to the peculiarities of this population, it is important to search for new and more comprehensive evaluation instruments. Level of Evidence II; Prognostic Studies; Prospective Study.